Gambel's Quail Survey Variability and Implications for Survey Design in the Mojave Desert. (1st July 2020) - Overton, Cory T.; Casazza, Michael L.; Connelly, Daniel; Gardner, Scott
ABSTRACT: Careful design of a wildlife population monitoring strategy is necessary to obtain accurate and precise results whether the purpose of the survey is development of habitat suitability models, to estimate abundance, or assess site occupancy. Important characteristics to consider in survey design are sources of elevated variability, particularly within‐subject variability, which increases the amount of data needed to achieve statistical certainty either in terms of population trend analysis, hypothesis testing, or statistical power. However, alternative objectives, such as associating counts with habitat characteristics, may benefit from increased variation among counts when differences covary with habitat measures. This difference can result in competing needs when developing survey protocols. We investigated the relative precision of differing gamebird monitoring protocols to identify methods with the greatest statistical efficiency. We assessed call‐count transects using standard Breeding Bird Survey protocols (Passive call‐counts) and modified by including longer survey periods and call playback (Active call‐counts), autonomous recording units with supervised call detection (ARU‐recorded calls), camera traps, and roadside covey‐counts for Gambel's quail ( Callipepla gambelii ) in the Mojave Desert (CA, USA) during the spring of 2016. Active call‐counts had the lowest within‐site variation relative to estimated population index values, but Passive call‐count transects may be more efficient for some purposes because more survey stations can be completed within a single survey timeframe. The ARU‐recorded calls may provide a suitable alternative despite larger sample size needs, especially for occupancy surveys because multiple units can be deployed concurrently. The ultimate sample size required will depend on specific study objectives and scope of interest, but camera traps and breeding‐season covey counts are not likely to meet objectives in desert environments. © 2020 The Wildlife Society. Abstract : Modified Breeding Bird Survey–style call‐count routes to index Gambel's quail in the Mojave Desert of California, USA, have the greatest potential statistical power. Call‐count methods and autonomous recording of quail calls may serve as suitable methods for long‐term studies into gamebird population change and habitat associations, but camera traps and route‐based covey counts are unlikely to provide meaningful results.